Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How can you show that the magnitude of the sample correlation coefficient is at most $1$?

The formula is huge, I'm not even sure how to approach this. Can anyone point me in the right direction?

Note that this is the sample correlation coefficient:

$$r_{xy} = \dfrac{\displaystyle \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})}{(n-1)s_xs_y} = \dfrac{\displaystyle \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})}{\sqrt{\displaystyle \sum_{i=1}^{n} (x_i - \bar{x})^2 \displaystyle \sum_{i=1}^{n} (y_i - \bar{y})^2}}$$

share|improve this question

2 Answers 2

up vote 3 down vote accepted

This follows from Cauchy–Schwarz inequality. The Cauchy–Schwarz inequality states that for any two vectors $a$ and $b$ in an inner product space, we have that $$\lvert \langle a, b \rangle \rvert^2 \leq \lvert \langle a, a \rangle \rvert \lvert \langle b, b \rangle \rvert$$ In your case, the vector $a$ is taken as $a_i = (x_i-\bar{x})$ and the vector $b$ is taken as $b_i = (y_i-\bar{y})$ and the inner product of $a$ and $b$ is taken as $\displaystyle \langle a, b \rangle = \sum_{i=1}^n a_i b_i$. Hence, we get that $$\displaystyle \langle a, b \rangle = \sum_{i=1}^n a_i b_i = \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})$$ $$\displaystyle \langle a, a \rangle = \sum_{i=1}^n a_i a_i = \sum_{i=1}^n (x_i - \bar{x})^2$$ $$\displaystyle \langle b, b \rangle = \sum_{i=1}^n b_i b_i = \sum_{i=1}^n (y_i - \bar{y})^2$$ Hence, by Cauchy–Schwarz inequality, we get that $$\left(\sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})\right)^2 \leq \left( \sum_{i=1}^n (x_i - \bar{x})^2 \right) \left( \sum_{i=1}^n (y_i - \bar{y})^2\right)$$ Taking the squareroot, we get that $$\left|\sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})\right| \leq \sqrt{\left( \sum_{i=1}^n (x_i - \bar{x})^2 \right) \left( \sum_{i=1}^n (y_i - \bar{y})^2\right)}$$ Hence, we can conclude that $$|r_{xy}| = \dfrac{\left|\displaystyle \sum_{i=1}^n (x_i - \bar{x})(y_i - \bar{y})\right|}{\displaystyle \sqrt{\left( \sum_{i=1}^n (x_i - \bar{x})^2 \right) \left( \sum_{i=1}^n (y_i - \bar{y})^2\right)}} \leq 1$$

EDIT

Proof of Cauchy Schwarz inequality:

First note that if the vector $b$ is zero, then the inequality is trivially satisfied since both sides are zero. Hence, we can assume that $b \neq 0$. Now look at the component of $a$ orthogonal to $b$ i.e. $$c = a - \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b$$ i.e. $$a = c + \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b$$ You can check that $c$ is orthogonal to $b$ by computing $$\langle c, b \rangle = \langle a,b \rangle - \dfrac{\langle a, b \rangle}{\langle b, b \rangle} \langle b, b \rangle = \langle a,b \rangle - \langle a,b \rangle = 0$$ You can also check that $\langle c, \alpha b \rangle = 0 = \langle \beta c, b \rangle$.

We now have that \begin{align} \langle a,a \rangle & = \left \langle c + \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b, c + \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b \right \rangle\\ & = \langle c,c \rangle + \left \langle c,\dfrac{\langle a, b \rangle}{\langle b, b \rangle} b \right \rangle + \left \langle \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b, c \right \rangle + \left \langle \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b, \dfrac{\langle a, b \rangle}{\langle b, b \rangle} b \right \rangle\\ & = \langle c,c \rangle + \left \lvert \dfrac{\langle a, b \rangle}{\langle b, b \rangle} \right \rvert^2 \langle b, b \rangle = \langle c,c \rangle + \dfrac{\left \lvert \langle a, b \rangle \right \rvert^2}{\langle b, b \rangle} \end{align} Now $\langle c,c \rangle \geq 0$. This gives that $$\langle a,a \rangle \geq \dfrac{\left \lvert \langle a, b \rangle \right \rvert^2}{\langle b, b \rangle}$$ Rearranging, we get what we want, namely $$\lvert \langle a, b \rangle \rvert^2 \leq \lvert \langle a, a \rangle \rvert \lvert \langle b, b \rangle \rvert$$

share|improve this answer
    
Thanks @DilipSarwate –  user17762 Jun 14 '12 at 23:26

Let $x=(x_1,\ldots,x_n), y=(y_1,\ldots,y_n), x' = (\bar x,\ldots,\bar x)$ and $y' = (\bar y,\ldots,\bar y)$. Using this, we can simplify notation by writing $$r_{xy}=\frac{\sum\limits_{i=1}^n(x_i-\bar x)(y_i-\bar y)}{\sqrt{\sum\limits_{i=1}^n(x_i-\bar x)^2\sum\limits_{i=1}^n(y_i-\bar y)^2}}\leq\frac{\sum\limits_{i=1}^n|x_i-\bar x||y_i-\bar y|}{\sqrt{\sum\limits_{i=1}^n(x_i-\bar x)^2\sum\limits_{i=1}^n(y_i-\bar y)^2}}=\frac{\|(x-x')(y-y')\|_1}{\|x-x'\|_2\|y-y'\|_2}$$ where $\|\cdot \|_1$ denotes the $L^1$ norm and $\|\cdot \|_2$ denotes the $L^2$ norm. We then only need that $$\|(x-x')(y-y')\|_1\leq\|x-x'\|_2\|y-y'\|_2$$ which follows from the Cauchy-Schwarz inequality.

share|improve this answer
1  
Don't you mean the $L^1$ and $L^2$ norms? The $2$-adic norm seems a bit out of place here... –  Erick Wong Jun 14 '12 at 22:56
    
@ErickWong Yes of course. Sometimes my thoughts run together. –  Alex Becker Jun 15 '12 at 0:02

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.